Experimental damage analysis in high loaded oscillating bearings. (October 2016) - Komba, E. Houara; Massi, F.; Bouscharain, N.; Le Jeune, G.; Berthier, Y.; Maheo, Y.
Abstract: Several industrial applications require rolling bearings to operate under both high load and oscillating motion. While the oscillating motion does not allow for EHD regime, the high load applied induces high contact pressures. Even if many works in the literature deal with rotating bearings, few works address high loaded oscillating bearings. The degradation scenario of high loaded oscillating bearings is here analysed step by step for both greased and ungreased bearings. Subsurface plastic damage of the balls was found to be at the origin of greased bearing degradation, while progressive superficial degradation lead to a faster degradation of ungreased bearings. Highlights: The degradation scenarios of greased and dry bearings are presented step by step. The degradation scenario is explained via experimental tests and surface analysis. The greased bearing damage is due to subsurface fatigue of the most loaded ball. The dry bearing damage consists in progressive superficial wear of contact pairs. The greased bearing lifetime is increased by the protective role of the grease.